The performance of innovation networks in transition economies: An empirical study of Slovenia - Ulrike Bross; Andrea Zenker (European Regional Science Association (ERSA), 1998)
Although the post-socialist countries in Eastern Europe experienced radical economic reforms, in many cases, the transformation of the industry sector has not been completed. As a result, the majority of enterprises is not internationally competitive and technological innovation is low. A model to foster innovation and competitiveness of Eastern European industries could be provided by western European regions with above-average growth rates during the last decades. The success of these regions, as is argued by an extensive literature on industrial districts, innovation networks and innovative milieux, relies on a special form of co-operation between companies from inside (and outside) the region. The aim of this paper is to assess the performance of networks and their impact on innovation activities in the transition context and to identify starting points for innovation policies. The empirical analysis is based on an extensive survey of industry and science in Slovenia. The theoretically guided empirical study of Slovenia further develops network analysis in the transformation context. Although Slovenia is one of the most developed transition economies, the socialist legacy, such as the fragmentation of research, applies to her as well. The first step assesses existing newly emerged and established networks in terms of type and quality of relations. As the opportunities of learning, technology transfer and innovating depend to some extend on the type of network, supplier-user relationships and horizontal networks between industry and science are distinguished. The quality of networks refers to their transactional and informational structure, trust relationships and regional dimensions. Special attention is on old versus new networks and their conduciveness to innovation: Whereas many actors in transition economies mourn about lost partnerships, these might hamper innovation. Therefore, the second step of this analysis documents the innovation performance of the sample. It relates the propensity of firms to engage in networks to the impact on process and product innovation. The third part is oriented towards policy recommendations. The Slovenian innovation policy is evaluated from the enterprises? point of view. This relies on the basis of the empirical analysis of the emergence of innovation networks and support by public programmes. The Ministry for Science and Technology has introduced various measures to realise the country?s innovation potential. The aim of the analysis is to suggest further improvements to effectively stimulate the development and consolidation of innovation networks. This benefits from extensive qualitative research carried out during the past years.
Keywords: 330